Identifikasi Komponen Volatil Tanaman Padi Fase Bunting dan Matang Susu sebagai Pakan Alami yang Disukai Tikus Sawah - Mardiah, Zahara; Sudarmaji, Sudarmaji (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2012)
Rat is a major rice pest that can detect and smell feed odor better then other mammals. Rice plants at booting and milky stages are the most commonly attacked by rats. These may be due to the preference of the rat to volatile compounds available in the plants at both growth stages. Analysis of the volatile compounds was conducted at the Flavor Analysis Laboratory of the Indonesian Center of Rice Research (ICRR), Sukamandi, by a Gas Chromatography Mass Spectrometry (GCMS) using the Solid Phase Microextraction (SPME) method. There were 54 volatile compounds identified from rice plants atbooting stage and 47 volatile compounds from that of milky stage. Descriptions of the volatile aromas contained in the rice plant at booting stage and milky stage were green, sweet, fatty, buttery, creamy, fruity, pungent sour, and beany.